2022
DOI: 10.18433/jpps33141
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Electronic Cigarettes and Liquid Nicotine Poisoning Exposure Cases in the United States

Abstract: Purpose: In 2007, electronic cigarettes (e-cigarette) were introduced as a smoking cessation device. Since then, its sale and marketing has been expanded annually. Concomitantly, there is an increase in the electronic cigarette (e-cigarette) and liquid nicotine exposure cases reported to the United States (US) poison control centers. The purpose of this review is to assess the exposure cases reported to US poison control centers to characterize the adverse health effects of e-cigarette and liquid nicotine use.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The purpose of an exposure assessment is to estimate the extent of public exposure to the emitted substance. In a study by Ayesha 23 , it was shown that accidental ingestion of e-liquids is also toxic to humans. Unintentional exposure in children and adults accounted for 87%, with intentional exposure 5% and unknown exposure < 1%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The purpose of an exposure assessment is to estimate the extent of public exposure to the emitted substance. In a study by Ayesha 23 , it was shown that accidental ingestion of e-liquids is also toxic to humans. Unintentional exposure in children and adults accounted for 87%, with intentional exposure 5% and unknown exposure < 1%.…”
Section: Methodsmentioning
confidence: 99%
“…E-cigarette liquids are packaged in quantities ranging from 10 to 50 ml, and in a study by Ayesha 23 , 64.8–92.5% of people were intoxicated by ingesting whole or partially leaked e-liquids. Due to the lack of patient data on acute exposure, we assumed an acute exposure of 10 ml of e-liquid for oral and dermal exposure to calculate the acute exposure to the hazardous substance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…E-cigarette liquids are packaged in quantities ranging from 10-50 ml, and in a study by Ayesha [23], 64.8-92.5% of people were intoxicated by ingesting whole or partially leaked e-liquids. Due to the lack of patient data on acute exposure, we assumed an acute exposure of 10 ml of e-liquid for oral and dermal exposure to calculate the acute exposure to the hazardous substance.…”
Section: Exposure Assessmentmentioning
confidence: 99%